CuO/TiO2 heterojunction composites: an efficient photocatalyst for selective oxidation of methanol to methyl formate. Issue 5 (14th January 2019) - Shi, Quanquan; Ping, Guicheng; Wang, Xiaojia; Xu, Hui; Li, Jingmei; Cui, Jiaqi; Abroshan, Hadi; Ding, Hongjing; Li, Gao
Abstract : This study demonstrates the synthesis of an efficient photocatalyst, CuO/TiO2 heterojunction, for selective aerobic photo-oxidation of methanol to methyl formate. Abstract : This study demonstrates the synthesis of an efficient photocatalyst, CuO/TiO2 heterojunction, for selective aerobic photo-oxidation of methanol to methyl formate. The CuO nanoparticles (size: 3.5 ± 1.0 nm) are particularly deposited at the {101} facet of anatase TiO2 nanosheets to minimize recombination of photo-generated electrons/holes. The photocatalysts are characterized by different methods, including powder X-ray diffraction (XRD), transmission electron microscopy (TEM), UV-vis spectroscopy, X-ray photoelectron spectroscopy (XPS), photoluminescence spectroscopy, and hydrogen temperature-programmed reduction (H2 -TPR). The heterojunction catalysts exhibit an excellent photocatalytic performance under mild conditions ( i.e., 25–45 °C and gas reactions under UV irradiation with a wavelength of 365 nm) for the selective photo-oxidation of methanol using 0.5 vol% oxygen (O2 ) as an oxidizing agent. The 5 wt% CuO/TiO2 photocatalyst exhibits a decent 95% methanol conversion with over 85% selectivity towards the formation of methyl formate. The by-product of the reaction is found to be merely CO2, which can be readily eliminated from the product. The formation rate for the methyl formate is 10.8 mmol g −1 h −1 at 25 °C, which is considerably higher than that for the corresponding CuO and TiO2 nanosheets as well as for conventional catalysts. The superior catalytic activity of the CuO/TiO2 is associated with its unique electronic structure and the synergistic effects at the interface of the photocatalysts' components. The results of this study offer guidelines for design of a new synthetic strategy for preparation of efficient photocatalysts for selective oxidation of methanol to methyl formate and related reactions.